If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1/4(3x+1)=2(2x-4)-8
We simplify the equation to the form, which is simple to understand
1/4(3x+1)=2(2x-4)-8
Simplifying:
+ 0.25*(3x+1)=2*(2x-4)-8
Reorder the terms in parentheses
+( + 0.75x + 0.25)=2*(2x-4)-8
Remove unnecessary parentheses
+ 0.75x + 0.25=+2+*(+2x-4+)-8
Reorder the terms in parentheses
+ 0.75x + 0.25=+(+4x-8)-8
Remove unnecessary parentheses
+ 0.75x + 0.25=+4x-8-8
We move all terms containing x to the left and all other terms to the right.
+ 0.75x-4x=-8-8-0.25
We simplify left and right side of the equation.
-3.25x=-16.25
We divide both sides of the equation by -3.25 to get x.
x=5
| 8x^2-5=11 | | 3(2-c)-12=-3c | | 0.3x-0.2(3-5x)=-0.5(x-6) | | -18-2x=2-8x | | x+3x+2=14 | | c=10n+26 | | r+16=15r-10 | | 10n+26=54 | | n^2-16n+36= | | w^2-26=0 | | 6y-1-4y=17 | | x/4+2=7 | | -69-2(7)(-7)= | | 3(5x-4)-6(5x-7)=0 | | 4-10x=-5 | | 2(9s+10)-3s=3(5s+2)-10 | | 234234X+234234X= | | 2.4+0.4x=0.25(6+x) | | 6(x+5)=3(2x+4)+18 | | .8(x+40)+.2x=57 | | 24x+5x+67=24 | | 5d^2+5d-6=0 | | 12(3x+3)-7(2x-3)=12x-13 | | a=1b | | X=32+-3x | | .70x+.05(2-x)=.10(-64) | | (p+36)+p+(4p-37)=677 | | 3x=x+36 | | 3x=x+32 | | (5-c)(5+c)=0 | | .30(12)+.05x=.10(6+x) | | 3(6-3m)+5(2m+7)=0 |